An in-cluster Sfp-type phosphopantetheinyl transferase instead of the holo-ACP synthase activates the granaticin biosynthesis under natural physiological conditions - Deng, Ming-Rong; Chik, Sin Yu; Li, Yan; Zhu, Honghui (Frontiers in Chemistry, 2022)
Bacterial aromatic polyketides are mainly biosynthesized by type II polyketide synthases (PKSs). The PKSs cannot be functional unless their acyl carrier proteins (ACPs) are phosphopantetheinylated by phosphopantetheinyl transferases (PPTases). Gra-ORF32 was identified as an in-cluster PPTase dedicated for granaticin biosynthesis in Streptomyces vietnamensis and the Arg- and Pro-rich N terminus was found to be crucial for catalytic activity. Overexpression of the encoding genes of the holo-ACP synthases of fatty acid synthases (FAS ACPSs) of both E. coli and S. vietnamensis could efficiently activate the production of granaticins in the Δgra-orf32 mutant, suggesting the ACP of granaticin (graACP) is an efficient substrate for FAS ACPSs. However, Gra-ORF32, the cognate PPTase of the graACP, could not compensate the conditional deficiency of ACPS in E. coli HT253, indicating that it has evolved to be functionally segregated from fatty acid biosynthesis. Nine out of eleven endogenous and all the tested exogenous non-cognate PPTases could activate the production of granaticins to varied extents when overexpressed in the Δgra-orf32 mutant, indicating that ACPs of type II PKSs could also be widely recognized as effective substrates by the Sfp-type PPTases. The exogenous PPTases of type II PKSs activated the production of granaticins with much higher efficiency, suggesting that the phylogenetically distant in-cluster PPTases of type II PKSs could share substrate preferences for the ACPs of type II PKSs. A significantly elevated production of granaticins was observed when the mutant Δgra-orf32 was cultivated on ISP2 plates, which was a consequence of crosstalk between the granaticin pathway and a kinamycin-like pathway as revealed by transcriptome analysis and pathway inactivations. Although the host FAS ACPS could efficiently activate the production of granaticins when overexpressed, only Gra-ORF32 activated the efficient production of granaticins under natural physiological conditions, indicating that the activity of the host FAS ACPS was strictly regulated, possibly by binding the FAS holo-ACP product with high affinity. Our findings would contribute to a more comprehensive understanding of how the ACPs of type II PKSs are activated and facilitate the future functional reconstitutions of type II PKSs in E. coli.